Developing Tools for Measuring Perception on Climate Change and its Impact on Insect-Pests of Major Staple Food Crops - Jaishi, M.; Kafle, K.; Subedi, R.; Khanal, A.; Poudel, A.; Paudel, R. (Journal of the Institute of Agriculture and Animal Science, 2018)
The climate change discourse has been evolving globally, and it has generated new ideas, debates and interests within the community of experts in local context too. People’s perceptions are critical components of the socio-cultural context within which people and societal system operate. People’s perception can compel or constrain social, economic cultural and political action to address particular risks and are liable of great influence. Present study is contemplated to construct a measuring tool to elucidate people’s perception about variability, causes, effect and impacts of climate change on production and productivity of major staple cereals of Nepal (Rice, maize wheat and potato) and standardized the same. Study was conducted on 15 different agro-ecological region of Nepal (n=900). As a result, screening and sorting from 105 statements collected and through content validation process final perception measuring instrument comprised of 70 statements was designed using equal appearing Likert scale. General criteria for perception scale construction related to item development, response set and statistical procedures are discussed. This scale was standardized for administration.